Rapid face detection using boosted simple features - Chan, Lih Sheng. (2009)
In recent years, face detection has attracted considerable interest from researchers and consumer-driven industries such as camera manufacturers. This computer technology identifies and locates human faces in an image regardless of position and scale. There are many applications based on face detection systems such as biometrics in facial recognition system, video surveillance and recent digital cameras for autofocus.